Analysis of the Effectiveness of Customs Services in the Perspective of Law in Indonesia - Jahir, Siska sanjahaya; Lubis, Tetty Melina; Lubis, Arief Fahmi (West Science Law and Human Rights, 2024)
This study aims to analyze the effectiveness of customs services in Indonesia from a legal perspective, utilizing a normative juridical approach. It examines the regulatory framework governing customs operations, identifies implementation gaps, and assesses enforcement mechanisms. Key areas of focus include bureaucratic inefficiencies, transparency issues, technological integration, and compliance enforcement. The findings highlight significant challenges in the current customs service framework, such as lengthy procedures, corruption, and inadequate use of technology. Recommendations are proposed to streamline procedures, enhance transparency, invest in technology, strengthen enforcement, and adopt international best practices. These improvements are essential for aligning Indonesia's customs services with international standards and supporting economic growth through enhanced trade facilitation.